A case report of the beneficial effects of botulinum toxin type A on Raynaud phenomenon in a patient with lung cancer. Issue 40 (October 2016) - Wang, Lu; Lei, Qi-song; Liu, Yu-ying; Song, Guan-jie; Song, Chun-ling
Abstract: Objective: Raynaud phenomenon is a vasospastic disorder affecting the hands and feet, and the efficacies of traditional treatments, such as pharmacological therapies and sympathectomy, are not uniform. Patients with paraneoplastic Raynaud phenomenon do not benefit from the traditional treatments. The use of botulinum toxin type A (BTX-A) for Raynaud phenomenon has been reported for several years; however, there are few reports regarding botulinum toxin type A in the treatment of paraneoplastic Raynaud phenomenon. We describe a case report of the beneficial effects of botulinum toxin type A on Raynaud phenomenon in a patient with lung cancer. Methods: A 63-year-old male complained of pain and discoloration of his fingers and indicated that oral nifedipine and low-dose aspirin were not effective. After approximately 8 months, he was diagnosed with lung cancer. Chemotherapy partially reduced the pain and discoloration of his fingers; however, no significant changes occurred in his fingers after the fourth cycle. We used BTX-A to treat this patient with paraneoplastic RP. A visual analogue scale (VAS) was used to assess the clinical response. Results: After approximately 2 months, the patient reported relief from pain, stiffness, numbness, and cold sensation. Furthermore, no local or general adverse effects were exhibited by the patient. Conclusion: This study used botulinum toxin type A for a patient with paraneoplastic Raynaud phenomenon. Botulinum toxin type A significantly improved the patient's clinical symptoms without significant complications. These findings suggest that BTX-A may represent a good option for the treatment of paraneoplastic RP.